Single-camera video production - Musburger, Robert B.; Ogden, Michael R. (Focal Press, 2014)
"Learn everything you need to know about creating video using the single-camera format, from preproduction planning to setting up, rehearsing, shooting, striking, and pleasing your audience. Harness lighting, audio, editing, and aesthetic techniques that will enhance the quality of your video projects and keep your clients coming back for more. Simple, elegant, and easy to use, Single-Camera Video Production, Sixth Edition is a staple in anyvideo artist's library. Whether you're just learning the basics of video production or you're a veteran who needs a refresher, this book provides you with a toolkit for understanding and implementing single-camera workflows, as well as how to use the single-camera format to its best advantage by emphasizing the importance of goals, audience analysis, and technology. This new edition has been updated to include: - Expanded sections on digital workflows, field and studio production, preproduction planning, audio, lighting, distribution, and nonlinear editing techniques - Detailed gear lists covering the latest camera, recorder, audio, lighting, and stabilization equipment used in the industry today - Fresh tips on creating video for your target audience and exhibition platform and shooting for the editing process - Insider career advice, including tips on how to get an internship, interviewing, finding a job, and earning a promotion - A companion website with video examples of the techniques discussed in the book as well as evolving updates on key technological shifts"--Provided by publisher.